Expectation Formation and Financial Ratio Adjustment Processes. - Lee, Cheng F.; Wu, Chunchi (The Accounting Review, 1988)
Abstract This paper analyzes the adjustment processes of financial ratios in the presence of costly adjustment and information uncertainty. The paper proposes a generalized partial adjustment-adaptive expectations model to characterize dynamic financial ratio adjustment processes. The proposed model incorporates the persistence of changes in industry averages into the process of financial ratio adjustment. The Gauss-Newton nonlinear regression method is used to estimate the structural parameters of the generalized model. Results show that adjustment to target ratios is not instantaneous. Results also show that there are differences in the patterns of ratio adjustment for firms in different industries with different sizes.